Cathemerality and Lunar Periodicity of Activity Rhythms in Owl Monkeys of the Argentinian Chaco - Fernandez Duque, Eduardo (2006)
Although most South American owl monkeys are mainly nocturnal, Aotus azarai azarai of the Argentinean Chaco regularly shows diurnal activity. In this study we examined the strong influence of moonlight on its diurnal and nocturnal activity, as well as the interaction of moonlight effects with other exogenous factors. We analyzed long-term automated activity recordings obtained with accelerometer collars from 7 owl monkeys during 2003 and 2004. Our data show marked lunar periodic and seasonal modulations of the owl monkeys’ activity pattern. On full moon days they were active throughout the whole night and displayed reduced activity during the day. With a new moon, activity decreased during the dark portion of the night, peaked during dawn and dusk and extended over the bright morning hours. Waxing and waning moons induced a significant increase in activity during the first and the second half of the night, respectively. During the cold winter months the monkeys displayed twice as much activity throughout the warmer bright part of the day than during the rest of the year. These findings indicate that A. a. azarai is mainly a dark-active species, but is still able to shift a considerable portion of activity into the bright part of the day if unfavourable lighting and/or temperature conditions prevail during the night.